Socioemotional wealth in family firms: A longitudinal content analysis of corporate disclosures. Issue 2 (June 2019) - Cleary, Peter; Quinn, Martin; Moreno, Alonso
Highlights: This study presents an analysis of the FIBER dimensions of SEW from a historic perspective, an approach we term SEW history. Using a content analysis of corporate disclosures, we develop a coding scheme based on the FIBER dimensions of SEW. Our results show FIBER dimensions change over time and differ between the two companies analysed. Context is a key point in the assessment of SEW. Abstract: Family business literature has noted the nature and presence of socioemotional wealth (SEW) in family firms. One method of observing SEW is by a five-dimension approach, collectively termed FIBER. While the dimensions are well defined, they have been critiqued, as have the theoretical foundations of SEW. Regardless, given the concept of SEW is about a decade old and the FIBER dimensions less so, it is reasonable to argue more research is needed. One potentially useful research approach is an historical one, which we will here term SEW history – the use of historical research to support (or question) the development of SEW as a concept. We undertake a content analysis of corporate disclosures through the Chairman's Statement of two Irish family breweries over a period of about two decades. To conduct the analysis, we develop a coding scheme based on the FIBER dimensions and offer some research propositions around these dimensions of SEW being stable (or not) over time. Our findings reveal that the Chairman's Statement does include FIBER dimensions in both breweries and they do change over time. Subsequent statistical analysis reveals significant differences in the FIBER dimensions between the two breweries and context is revealed as a key issue in the assessment of SEW, something prior research has noted. The study also raises some questions on the nature of some FIBER dimensions, in particular the "I" dimension.